Glutathione S-Transferase Alpha 4 Promotes Proliferation and Chemoresistance in Colorectal Cancer Cells - Zhang, Zhanhu; Xu, Lili; Huang, Lin; Li, Tianqi; Wang, Jane Y.; Ma, Chunhua; Bian, Xiaoyun; Ren, Xiaoyan; Li, Haibo; Wang, Xingmin (Frontiers in Oncology, 2022)
Glutathione S-transferase alpha 4 (GSTA4) is a phase II detoxifying enzyme that is overexpressed in colorectal cancer (CRC) regulated by oncogenic transcription factor AP-1. However, the roles of GSTA4 in the CRC cells is unclear. In the present study we investigated the roles of GSTA4 in the CRC cells by inactivating GSTA4 in HCT116 human CRC cells (Defined as HCT116ΔGSTA4) using the CRISPR/Cas9 gene editing. Cell proliferation, clonogenicity, and susceptibility to chemotherapeutic drugs were analyzed in vitro and in a xenograft model. The results showed that loss of GSTA4 significantly decreased cell proliferation and clonogenicity whereas it increased intracellular reactive oxygen species and cell susceptibility to 5-fluorouracil (5-FU) and oxaliplatin. In addition, exposure of HCT116ΔGSTA4 cells to 5-FU increased expression of γH2AX, a hallmark for double stranded DNA break. In contrast, no remarkably increased γH2AX was noted in oxaliplatin-treated HCT116ΔGSTA4 cells compared to HCT116 cells. Moreover, loss of GSTA4 blocked AKT and p38 MAPK pathways leading to proliferative suppression. Finally, xenograft model showed decreased tumor size for HCT116ΔGSTA4 cells compared to HCT116 cells confirming in vitro findings. These findings suggest that GSTA4 is capable of promoting proliferation, tumorigenesis, and chemoresistance and may be a potential target for CRC therapy.